Differentiation in cereal production among Member States of the European Union - Nowak, Anna (Polish Journal of Agronomy, 2020)
The paper aimed at evaluating spatial differentiation and trends in changes in the level and structure of cereal production in the European Union. The significance of the undertaken studies is a result of the growing requirement for cereals and a high cereal production potential, thanks to which respective member states are able to compete on the global market. This paper is based on the statistical and tabular analysis of EUROSTAT database pertaining to years 2007–2016. It provided grounds for calculating the selected indicators of changes in the cereal production level and structure as well as the roles of respective member states in the EU production of major cereals. The surveys showed fluctuations in the value of cereal production in the study period. A high increase was recorded in the value of wheat production (20.4%) in 2016 in comparison to that in 2007. The total area under cereal crops in the EU slightly decreased. The largest producers of cereals in the EU are France, Germany, Poland, Spain and the United Kingdom – in 2016 those states produced 58% of the total cereal crops. In addition, studies show that EU member states differ in terms of technological yield of cereals measured as yield per 1 ha. The average yield of cereals in 2016 ranged from 82.2 dt ha-1 in Ireland to 21.9 dt ha-1 in Cyprus.